KERAPUHAN IDENTITAS RAS KULIT HITAM AFRIKA DALAM PUISI THE LITTLE BLACK BOY KARYA WILLIAM BLAKE - Neisya, Neisya (Jurnal Ilmiah Bina Bahasa, 2018)
Colonialism always leave a long-standing paradigm complexity in the period after colonialism. The issue of identity becomes important because it shows the existence of a person in the community. This study intends to examine the post-colonial discourse in The Little Black Boy poem by William Blake. In analyzing, the author uses Bhabha's resistence of the orient approach to explore the fragility or confusion of identity experienced by the little Black Boy due to the racism that he got from white people. The results of this study indicate that the little Black Boy in essence feels so inferior because he is considered not good because of his black physical identity. He rejects the notion that black means evil and white means good, but assumes that everything is the same in God's eyes because in the end all humans will return to God.